2021
DOI: 10.1038/s41436-020-00981-2
|View full text |Cite
|
Sign up to set email alerts
|

The broad phenotypic spectrum of PPP2R1A-related neurodevelopmental disorders correlates with the degree of biochemical dysfunction

Abstract: Purpose: Neurodevelopmental disorders (NDD) caused by protein phosphatase 2A (PP2A) dysfunction have mainly been associated with de novo variants in PPP2R5D and PPP2CA, and more rarely in PPP2R1A. Here, we aimed to better understand the latter by characterizing 30 individuals with de novo and often recurrent variants in this PP2A scaffolding Aα subunit. Methods: Most cases were identified through routine clinical diagnostics. Variants were biochemically characterized for phosphatase activity and interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(78 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…In brief, the PPP2R1A variant was verified as a de novo change, with both maternity and paternity confirmed via in-silico analysis of trio ES data and end-point PCR of loci with high population minor allele frequency used to compare inherited genotypes (C. R. . This variant was absent from large-scale population databases (Karczewski et al 2020), has been reported in the literature with supporting in-vitro functional studies suggesting a reduction in protein activity (Houge et al 2015;Ji et al 2019) hindering binding to the regulatory subunit B55α encoded by PPP2R2A (Lenaerts et al 2021) and is predicted to be damaging by multiple computational (in silico) functional prediction algorithms (ACMG/AMP: PS2, PM2, PM_PS3, PP3). The PPP2R1A variant was verified via orthogonal Sanger sequencing of proband and parental samples and observed only in the proband sample.…”
Section: -Genomic Analyses and Variant Interpretationsupporting
confidence: 62%
“…In brief, the PPP2R1A variant was verified as a de novo change, with both maternity and paternity confirmed via in-silico analysis of trio ES data and end-point PCR of loci with high population minor allele frequency used to compare inherited genotypes (C. R. . This variant was absent from large-scale population databases (Karczewski et al 2020), has been reported in the literature with supporting in-vitro functional studies suggesting a reduction in protein activity (Houge et al 2015;Ji et al 2019) hindering binding to the regulatory subunit B55α encoded by PPP2R2A (Lenaerts et al 2021) and is predicted to be damaging by multiple computational (in silico) functional prediction algorithms (ACMG/AMP: PS2, PM2, PM_PS3, PP3). The PPP2R1A variant was verified via orthogonal Sanger sequencing of proband and parental samples and observed only in the proband sample.…”
Section: -Genomic Analyses and Variant Interpretationsupporting
confidence: 62%
“…Most recently, a broad phenotypic spectrum of PPP2R1A-related neurodevelopmental disorder in 30 individuals found language delay, hypotonia, and hypermobile joints along developmental delay ranging from mild learning to severe intellectual disabilities (ID) with or without epilepsy. Individuals without B55α subunit-binding deficit had macrocephaly, less severe ID, and no seizures while impaired B55α but increased striatin binding were found biochemically more disruptive variants with associated profound ID, epilepsy, hypoplasia of corpus callosum, and occasionally microcephaly [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…HR11 to HR15 anchors PP2A-C, while the variable regulatory B subunit binds to HR1 to HR10. Recent WGS and WES studies (Houge et al, 2015;Lenaerts et al, 2021;Wallace et al, 2019;Zhang et al, 2020) have reported a total of 16 SNVs on the PP2A-Aα isoform (Fig. 2A, red; Table S1).…”
Section: The Scaffolding Pp2a-a Subunitmentioning
confidence: 99%